Amortisation versus impairment of goodwill and accounting quality - Paul Van Hulzen; Laura Alfonso; Georgios Georgakopoulos; Ioannis Sotiropoulos (International Journal of Economic Sciences and Applied Research, 2011)
In this paper there has been made a comparison between the amortisation and the impairment methods for accounting for goodwill, with regards to their associated effects on accounting quality. Based on two qualitative characteristics of accounting information, as formulated by the International Accounting Standards Board (IASB), the effects of the new impairment method are examined using a value relevance and a timeliness model. The sample consists of European companies that adopted this new method of goodwill accounting, following the required adoption of the International Financial Reporting Standards (IFRS) in 2005. The results indicate that impairment of goodwill is actually less value relevant than amortisation, but that it does lead to more timely accounting information. It is concluded that the objective of the IASB in issuing a new accounting standard is not completely met and it only partially contributes to higher accounting quality.
Keywords: M21; M41; M48; 330; amortisation; impairment; goodwill; value relevance; timeliness